Simplified prosthetic rehabilitation of a patient with partial finger amputation after a firearm injury - Penitente, Paulo Augusto [UNESP]; Da Silva, Emily Vivianne Freitas [UNESP]; Tabata, Lucas Fernando; Goiato, Marcelo Coelho [UNESP]; De Medeiros, Rodrigo Antonio (Wolters Kluwer, 2022)
Objective:This study reports a clinical case of rehabilitation of a patient who had her left little finger amputated at the mesial phalanx because of a gunshot wound. The finger prosthesis was custom- made using a silicone.Case description:This study presents a clinical case of a female patient who had her left little finger amputated at the mesial phalanx because of a gunshot wound in 2016. The patient was attended at a reference center in maxillofacial rehabilitation in the city of Brasilia, Distrito Federal, Brazil, for the manufacture of a finger prosthesis. After molding, a finger waxing was obtained using the right little finger as a template. The waxing was later adjusted on the plaster model of the affected stump. The prosthesis was manufactured with silicone and intrinsically stained with a makeup powder. A water-based adhesive and a ring were used to generate a slight compression so that the prosthesis was retained on the stump.Outcomes:The rehabilitation showed satisfactory levels of stability, retention, and aesthetics, and it was usable and clinically acceptable, as observed in a follow-up appointment in February 2020.Conclusions:The complete or partial reestablishment of functions performed by important structures, such as the fingers, is essential to increase the quality of life of individuals, improving their performance of daily activities. In addition, reporting on this public health problem allows scientific advancement in the area.
Keywords: amputation stumps; artificial limbs; quality of life; silicones